Hubungan Antara Efikasi Diri dengan Kesiapan Kerja pada Mahasiswa Tingkat Akhir Tahun 2017: The Relationship Between Self-Efficacy and Work Readiness in Final Level Students Class of 2017 - Fika Rizki Amaliah; Ririn Dewanti Samudera Indriani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: University graduates face increasing challenges in entering the labor market, requiring adequate psychological readiness alongside academic competence. Specific Background: Work readiness among final-year students is closely related to internal psychological factors, particularly self-efficacy, which reflects an individual’s belief in their capability to perform tasks and achieve goals. Knowledge Gap: Although previous studies have examined self-efficacy and work readiness, limited empirical evidence specifically addresses final-year psychology students at Universitas Muhammadiyah Sidoarjo. Aims: This study aimed to determine the relationship between self-efficacy and work readiness among final-year students. Results: Using a quantitative correlational design with 103 students selected from a population of 140, data were analyzed using Pearson Product Moment correlation. The findings revealed a significant positive correlation between self-efficacy and work readiness (r = 0.915; p < 0.05), with an R Square value of 0.719, indicating that 71.9% of work readiness variance is associated with self-efficacy. Novelty: This study provides empirical evidence within the specific context of final-year psychology students in an Indonesian private university. Implications: Strengthening self-efficacy through institutional support and structured training programs may contribute to improving students’ preparedness for workforce transition. Keywords: Self Efficacy, Work Readiness, Final Year Students, Quantitative Correlational Study, Higher Education Key Findings Highlights A strong positive correlation was identified between psychological belief in capability and employment preparedness. Statistical analysis demonstrated a substantial proportion of variance explained by the independent variable. Most respondents were categorized in moderate to low levels of employment preparedness.